2003
DOI: 10.1667/rr3081
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Localization of Superoxide Dismutase is Required for Decreasing Radiation-Induced Cellular Damage

Abstract: We investigated the importance of mitochondrial localization of the SOD2 (MnSOD) transgene product for protection of 32D cl 3 hematopoietic cells from radiation-induced killing. Four plasmids containing (1) the native human copper/zinc superoxide dismutase (Cu/ZnSOD, SOD1) transgene, (2) the native SOD2 transgene, (3), the SOD2 transgene minus the mitochondrial localization leader sequence (MnSOD-ML), and (4) the SOD2 mitochondrial leader sequence attached to the active portion of the SOD1 transgene (ML-Cu/ZnS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(149 citation statements)
references
References 37 publications
4
143
0
2
Order By: Relevance
“…MnSOD has been described by many investigators as being an effective endogenous antioxidant enzyme capable of conferring enhanced radiation resistance to cells [4,5,8,10]. Since maximal elevation of MnSOD occurs between 16 and 24 h following exposure of cells to WR1065, it was of interest to determine whether irradiation of cells at this time would result in an enhanced cellular resistance to the cytotoxic effects of ionizing radiation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…MnSOD has been described by many investigators as being an effective endogenous antioxidant enzyme capable of conferring enhanced radiation resistance to cells [4,5,8,10]. Since maximal elevation of MnSOD occurs between 16 and 24 h following exposure of cells to WR1065, it was of interest to determine whether irradiation of cells at this time would result in an enhanced cellular resistance to the cytotoxic effects of ionizing radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the role of mitochondrial damage leading to cell death, overexpression of MnSOD in cells induced by tranfection of an MnSOD transgene gives rise to an enhanced radioresistance and to an inhibition of radiation-induced apoptosis [8][9][10]. Furthermore, it has been demonstrated that localization of superoxide dismutase within the mitochondria is a requirement for subsequent radioprotection against cellular damage [4].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations